Composite material, preparation method thereof and luminescent device

By compounding the transmission material of organic empty acupoints with the transition metal oxide, and using the light treatment method to generate transition metal oxides in situ, the problem of poor thermal stability of organic empty acupoint transmission materials is solved. Poor acupoint injection and transmission performance.

CN119384154APending Publication Date: 2025-01-28GUANGDONG JUHUA RES INST OF ADVANCED DISPLAY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310935475.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Because organic hole transport materials are easily destroyed after being heated, they lead to poor thermal stability, which affects their application.

Method used

By compounding the transmission material of organic empty acupoints with the transition metal oxide, the price band of the transition metal oxide is higher than that of the organic cave transmission material, forming a composite material, and the transition metal oxide is generated in situ in situ.

Benefits of technology

Improve the stability of the composite materials and the injecting and transmission performance of the acupoints, reduce the power of the acupoint injection, and enhance the performance of the luminous device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384154A_ABST
    Figure CN119384154A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material, a preparation method thereof and a light-emitting device. According to the composite material, through compounding of the organic material and the inorganic material, namely compounding of the organic hole transport material and the transition metal oxide, the stability of the composite material is improved, and the valence band energy level of the transition metal oxide is higher than that of the organic hole transport material, so that when the transition metal oxide is used as a material of a hole function layer, the hole function layer is more stable. The valence band energy level of the transition metal oxide is between the valence band energy level of the organic hole transport material and the valence band energy level of the anode, hole injection barriers can be reduced, and hole injection and transport performance can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optoelectronic technology, and in particular to a composite material and a preparation method thereof, and a light-emitting device. Background Art

[0002] Organic hole transport materials are widely used as materials for hole functional layers of optoelectronic devices such as OLEDs, QLEDs, and solar cells due to their good hole mobility and processability. However, organic hole transport materials have poor thermal stability, which affects their application because their organic structure is easily destroyed after being heated. Summary of the invention

[0003] In view of this, the present application provides a composite material and a preparation method thereof, and a light-emitting device, aiming to provide a composite material that has good hole mobility and good stability.

[0004] The embodiment of the present application is implemented by providing a composite material, including an organic hole transport material and a transition metal oxide, wherein the valence band energy level of the transition metal oxide is higher than the valence band energy level of the organic hole transport material.

[0005] Optionally, in some embodiments of the present application, a negatively charged organic group is connected to the transition metal oxide, and the organic group is selected from one or more of the following structures:

[0006]

[0007] Wherein, R1, R3, and R4 are independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0008] R2 and R5 are selected from one or more combinations of H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0009] The substituent is selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkyl acyloxy, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, C3-C10 cycloalkyl; n is an integer of 0-4, and m is an integer of 0-6.

[0010] An embodiment of the present application also provides a method for preparing a composite material, comprising: providing a first mixture, wherein the first mixture comprises an organic hole transport material and a first solvent; after subjecting the first mixture to a first light treatment, adding an organic transition metal salt to the first mixture, and continuing to subject the first mixture to a second light treatment to obtain a composite material; wherein the valence band energy level of the transition metal oxide corresponding to the organic transition metal salt is higher than the valence band energy level of the organic hole transport material.

[0011] An embodiment of the present application also provides a light-emitting device, comprising: a first electrode and a second electrode arranged opposite to each other; a light-emitting layer arranged between the first electrode and the second electrode; a hole functional layer arranged between the first electrode and the light-emitting layer; wherein the material of the hole functional layer includes the above-mentioned composite material, or includes a composite material obtained by the preparation method of the above-mentioned composite material.

[0012] The embodiment of the present application also provides a method for preparing a light-emitting device, the method comprising: providing a preset device, the preset device comprising a first electrode; arranging a hole functional material on the preset device to form a hole functional layer; forming a stacked light-emitting layer and a second electrode on the hole functional layer to obtain a light-emitting device;

[0013] Alternatively, the preparation method includes: providing a prefabricated device, the prefabricated device including a stacked second electrode and a light-emitting layer; arranging a hole functional material on the prefabricated device to form a hole functional layer; forming a stacked first electrode on the hole functional layer to obtain a light-emitting device; wherein the hole functional material includes the composite material as described above, or includes a composite material obtained by the preparation method of the composite material as described above.

[0014] The embodiments of the present application further provide a display device, comprising the light-emitting device as described above, or comprising a light-emitting device manufactured by the method for manufacturing the light-emitting device as described above.

[0015] The composite material of the present application improves the stability of the composite material by combining an organic material with an inorganic material, that is, combining an organic hole transport material with a transition metal oxide. The valence band energy level of the transition metal oxide is higher than the valence band energy level of the organic hole transport material. Therefore, when used as a material for a hole functional layer, the valence band energy level of the transition metal oxide is between the organic hole transport material and the anode, which can reduce the hole injection barrier and improve the hole injection and transport performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a composite material provided in the present application;

[0018] Figure 2 A structural schematic diagram of an embodiment of a light emitting device is provided for the present application.

[0019] Figure 3 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;

[0020] Figure 4 A schematic diagram of another embodiment of a method for preparing a light-emitting device provided in the present application;

[0021] Figure 5 and Figure 6 AFM images of the hole functional layer in device comparative example 1 and device embodiment 2 respectively;

[0022] Figure 7 EQE-storage time diagram of device embodiments 2 and 12 and device comparative examples 1 and 4;

[0023] Figure 8 and Fig. 9 JV curves of single hole devices of device embodiments 1-13 and comparative examples 1-4;

[0024] Figure 10-13 These are the valence band energy level diagrams of copper oxide, molybdenum oxide, manganese oxide and cobalt oxide respectively.

[0025] Reference numerals: light emitting device 100 ; first electrode 10 ; second electrode 20 ; light emitting layer 30 ; hole functional layer 40 ; electron functional layer 50 , electron injection layer 51 , electron transport layer 52 . DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.

[0027] In the present application, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In the present application, "at least one" refers to one or more, and "plurality" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc or abc, where a, b, c can be single or multiple, respectively.

[0028] In the present application, "substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted and no additional definition is provided, "substituted" means that the hydrogen of the compound or group is replaced by a substituent such as a deuterium atom, a halogen, a hydroxyl group, a nitro group, a cyano group, an isocyano group, an amino group, an azido group, an amidino group, a hydrazine group, a hydrazone group, a carbonyl group, a carbamoyl group, a thiol group, an ester group, a carboxyl group or a salt thereof, a sulfonic acid group or a salt thereof, a phosphate group or a salt thereof, a silyl group, a C1-C20 alkyl group, a C2-C20 alkenyl group, a C2-C20 alkynyl group, a C6-C30 aryl group, a C7-C30 aralkyl group, a C1-C30 alkoxy group, a C1-C20 heteroalkyl group, a C3-C20 heterocyclic group, a C3-C20 heteroaralkyl group, a C3-C30 cycloalkyl group, a C3-C15 cycloalkenyl group, a C6-C15 cycloalkynyl group, a C3-C30 heterocycloalkyl group, or a combination thereof.

[0029] In the present application, aryl, aromatic group, aromatics, aromatic ring system have the same meaning and can be interchanged. In the present application, heteroaryl, heteroaromatic group, heteroaromatics, heteroaromatic ring system have the same meaning and can be interchanged. In the present application, "ring atoms number" represents the number of atoms of the ring atoms constituting the ring itself in the structural compound (for example, monocyclic compound, condensed ring compound, cross-linked compound, carbocyclic compound, heterocyclic compound) obtained by atoms bonding into a ring shape, i.e. the number of atoms forming the ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. About "ring atoms number" described below, it is the same under the condition that there is no special explanation. For example, the ring atoms number of benzene ring is 6, the ring atoms number of naphthalene ring is 10, and the ring atoms number of thienyl is 5.

[0030] In the present application, "aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "substituted or unsubstituted aromatic groups having 6 to 30 ring atoms" refers to aromatic groups containing 6 to 30 ring atoms, and the aromatic group can be optionally further substituted. Preferably, substituted or unsubstituted aromatic groups having 6 to 24 ring atoms are used, more preferably substituted or unsubstituted aromatic groups having 6 to 18 ring atoms are used, and particularly preferably substituted or unsubstituted aromatic groups having 6 to 14 ring atoms are used, and the aromatic group can be optionally further substituted; suitable examples include, but are not limited to, phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, fluoranthenyl, triphenylene, pyrenyl, perylene, naphthyl, fluorenyl, dinaphthylenyl, acenaphthene and derivatives thereof. It is understandable that multiple aromatic groups may also be interrupted by short non-aromatic units (e.g. <10% non-H atoms, such as C, N or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamine, diaryl ether systems should also be included in the definition of aromatic groups.

[0031] In the present application, "heteroaryl or heteroaromatic group" means that at least one carbon atom is replaced by a non-carbon atom on the basis of an aromatic group, and the non-carbon atom can be an N atom, an O atom, an S atom, an Si atom, a P atom, etc. For example, "substituted or unsubstituted heteroaryl having 5 to 30 ring atoms" means a heteroaryl having 5 to 30 ring atoms, preferably a substituted or unsubstituted heteroaryl having 5 to 24 ring atoms, more preferably a substituted or unsubstituted heteroaryl having 5 to 18 ring atoms, and particularly preferably a substituted or unsubstituted heteroaryl having 5 to 14 ring atoms, and the heteroaryl is optionally further substituted; suitable examples include, but are not limited to: thienyl, furanyl, pyrrolyl, oxadiazolyl, triazolyl, imidazolyl, pyridyl, bipyridyl, pyrimidyl, Triazine, acridinyl, pyridazinyl, pyrazinyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, benzothiophenyl, benzofuranyl, indolyl, pyrroloimidazolyl, pyrrolopyrrolyl, thienopyrrolyl, thienothiphenyl, furopyrrolyl, furofuranyl, thienofuranyl, benzisoxazolyl, benzisothiazolyl, benzimidazolyl, o-naphthyl, phenanthridinyl, primary pyridyl, quinazolinone, dibenzothiophenyl, dibenzofuranyl, carbazolyl and derivatives thereof.

[0032] In the present application, "chain alkyl" may mean a straight chain or a chain alkyl having a branch. The carbon number of the alkyl group may be 1 to 30, 1 to 20, 1 to 10 or 1 to 6. A phrase containing this term, for example, "C1 to C30 chain alkyl" means a chain alkyl group containing 1 to 30 carbon atoms, and each occurrence may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, and finally C30 alkyl. Non-limiting examples of alkyl radicals include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, 2-ethylbutyl, 3,3-dimethylbutyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, 1-methylpentyl, 3-methylpentyl, 2-ethylpentyl, 4-methyl-2-pentyl, n-hexyl, 1-methylhexyl, 2-ethylhexyl, 2-butylhexyl, n-heptyl, 1-methylheptyl, 2,2-dimethylheptyl, 2-ethylheptyl, 2-butylheptyl, n-octyl, tert-octyl, 2-ethyloctyl, 2-butyloctyl, 2-hexyloctyl, 3,7-dimethyloctyl, n-nonyl, n-decyl, adamantyl, 2-ethyldecyl, 2-butyldecyl, 2-hexyldecyl, 2-octyl decyl, n-undecyl, n-dodecyl, 2-ethyldodecyl, 2-butyldodecyl, 2-hexyldodecyl, 2-octyldodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, 2-ethylhexadecyl, 2-butylhexadecyl, 2-hexylhexadecyl, 2-octylhexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, n-eicosyl, 2-ethyleicosyl, 2-butyleicosyl, 2-hexyleicosyl, 2-octyleicosyl, n-heneicosyl, n-docosyl, n-tricosyl, n-tetracosyl, n-pentacosyl, n-hexacosyl, n-heptacosyl, n-octacosyl, n-nonacosyl, n-triacontyl, and the like.

[0033] In the present application, "cycloalkyl" means a cyclic alkyl group, and "C3-C30 cycloalkyl" means a cycloalkyl group containing 3 to 30 carbon atoms, and each occurrence can be independently C3 cycloalkyl, C4 cycloalkyl, C5 cycloalkyl, C6 cycloalkyl, C7 cycloalkyl, and up to C30 cycloalkyl. Non-limiting examples of cycloalkyl groups include cyclopentyl, cyclohexyl, 4-methylcyclohexyl, 4-tert-butylcyclohexyl, cyclooctyl, and the like. In the present application, "alkenyl" means a chain olefin, and "C2-C30 alkenyl" means an alkenyl group containing 2 to 30 carbon atoms. Non-limiting examples of alkenyl groups include ethenyl, propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, and the like. In the present application, "cycloalkenyl" means a cyclic alkene, "C3-C30 cycloalkenyl" means a cycloalkenyl containing 3-30 carbon atoms, and non-limiting examples of cycloalkenyl include cyclopentene, cyclohexene, 4-methylcyclohexene, 4-tert-butylcyclohexene, etc. In the present application, "alkynyl" means a chain alkyne, "C2-C30 alkynyl" means an alkynyl containing 2-30 carbon atoms, and non-limiting examples of alkynyl include ethynyl, propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentynyl, etc. In the present application, "cycloalkynyl" means a cyclic alkyne, "C6-C30 cycloalkynyl" means a cycloalkynyl containing 6-30 carbon atoms, and non-limiting examples of cycloalkynyl include cyclohexyne, cycloheptyne, cyclooctyne, etc. In the present application, "alkoxy" refers to a group with a structure of "-O-alkyl", that is, a chain alkyl or cycloalkyl group as defined above connected to other groups via an oxygen atom. "C1-C30 alkoxy" refers to an alkoxy group in which an alkyl group of 1 to 30 carbon atoms is connected to an oxygen atom. Suitable examples of phrases containing this term include, but are not limited to, methoxy (-O-CH3 or -OMe), ethoxy (-O-CH2CH3 or -OEt) and tert-butoxy (-OC(CH3)3 or -OtBu). In the present application, "alkoxycarbonyl" refers to a carbonyl group substituted by an alkoxy group, and "C1-C10 alkoxycarbonyl" refers to a carbonyl group substituted by an alkoxy group of C1-C10, wherein the alkoxy group is as defined above. Suitable examples of phrases containing this term include, but are not limited to, methoxycarbonyl (-CO-OCH3), ethoxycarbonyl (-CO-OCH2CH3) and tert-butoxycarbonyl (-CO-OC(CH3)3). In the present application, "alkylthio" refers to a group having a structure of "-S-alkyl", i.e., a chain alkyl or cycloalkyl group as defined above connected to other groups via a sulfur atom. Phrases containing this term, suitable examples include, but are not limited to: methylthio (-S-CH3 or -SMe), ethylthio (-S-CH2CH3 or -S-Et) and tert-butylthio (-SC(CH3)3 or -S-tBu).

[0034] The present application provides a composite material, comprising an organic hole transport material and a transition metal oxide, wherein the valence band energy level of the transition metal oxide is higher than the valence band energy level of the organic hole transport material.

[0035] In this embodiment, the stability of the composite material is improved by combining organic materials with inorganic materials, that is, combining organic hole transport materials with transition metal oxides. The valence band energy level of the transition metal oxide is higher than that of the organic hole transport material. Therefore, when used as a material for a hole functional layer, the valence band energy level of the transition metal oxide is between the organic hole transport material and the anode, which can reduce the hole injection barrier and improve the hole injection and transport performance.

[0036] In one embodiment, the valence band energy level of the organic hole transport material can be -5.2 to -5.4 eV. Further, the organic hole transport material can include N,N'-dinaphthyl-N,N'-diphenylbenzidine, N,N'-bis-(3-methylphenyl)-N,N'-bis-(phenyl)-benzidine), 4,4',4"-tris(N-3-methylphenyl-N-phenyl-amino)-triphenylamine, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(N,N'-bis(4-butylphenyl)-N,N' -bis(phenyl)benzidine), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazole-9-yl)triphenylamine, 4,4'-di(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine.

[0037] In this embodiment, the organic hole transport material can make the composite material have better hole injection and transport properties. In one embodiment, the valence band energy level of the transition metal oxide can be -4.7 to -5.4eV, specifically -4.80 to -5.25eV, -4.86 to -5.20eV, -4.86 to -5.16eV, -5.00 to -5.16eV, etc. Further, the transition metal oxide includes one or more of copper oxide, cobalt oxide, molybdenum oxide, and manganese oxide. In one embodiment, the average particle size of the transition metal oxide is 3 to 10nm, specifically 3 to 8nm, 4 to 8nm, 4 to 6nm, 5 to 6nm, etc.

[0038] In one embodiment, the surface of the transition metal oxide is connected to a negatively charged organic group, and the organic group is selected from one or more of the following structures:

[0039]

[0040] Wherein, R1, R3, and R4 are independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0041] R2 and R5 are selected from one or more combinations of H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0042] The substituent is selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkyl acyloxy, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, and C3-C10 cycloalkyl;

[0043] n is an integer of 0-4, and m is an integer of 0-6.

[0044] In this embodiment, the organic group is coordinated and connected to the surface of the transition metal oxide, and can combine with a large number of oxygen defects on the surface of the transition metal oxide, reduce the surface defects of the transition metal oxide, increase the dispersibility of the transition metal oxide, and improve the film-forming property of the composite material. In addition, the organic group is coordinated and connected to the surface of the transition metal oxide, which can also increase the carrier concentration and improve the hole transport performance.

[0045] In one embodiment, n is selected from any integer of 0, 1, 2, 3 and 4, and m is selected from any integer of 0, 1, 2, 3, 4, 5 and 6. In one embodiment, n is selected from 0 or 1. In one embodiment, m is selected from 0.

[0046] In one embodiment, R1, R3, and R4 are independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C10 alkyl, substituted or unsubstituted C3-C10 cycloalkyl, substituted or unsubstituted C2-C10 alkenyl, substituted or unsubstituted C3-C10 cycloalkenyl, substituted or unsubstituted aryl having 6-12 ring atoms, and substituted or unsubstituted heteroaryl having 5-12 ring atoms.

[0047] In one embodiment, the substituent is selected from one or more of a C1-C10 alkyl acyloxy group, a C1-C10 alkoxycarbonyl group, a C1-C10 chain alkyl group, and a C3-C10 cycloalkyl group.

[0048] In one embodiment, each occurrence of R1, R3, and R4 is independently selected from H, one or more of the following structures:

[0049]

[0050] Wherein, each occurrence of R6 is selected from one or more of H, D, and C1-C10 alkyl; n1 is an integer of 0-4, and n2 is an integer of 0-10; each occurrence of R7 is selected from H, D, C1-C10 alkyl, -C(=O)-(CH2) m5 -CH3, m1 is an integer of 0 to 5, m2 is an integer of 0 to 7, m3 is an integer of 0 to 4, and m5 is an integer of 0 to 5.

[0051] Specifically, n1 can be selected from any integer of 0, 1, 2, 3, and 4. n2 can be selected from any integer of 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10. m1 can be selected from any integer of 0, 1, 2, 3, 4, and 5, m2 can be selected from any integer of 0, 1, 2, 3, 4, 5, 6, and 7, m3 can be selected from any integer of 0, 1, 2, and 3, and m5 can be selected from any integer of 0, 1, 2, 3, 4, and 5.

[0052] Furthermore, the organic group may include one or more of the following structural formulas:

[0053]

[0054] In one embodiment, the mass ratio of the transition metal oxide to the organic hole transport material is 5-25%, specifically 5-20%, 10-20%, 10-15%, 5-10%, 20-25%, etc. The mass ratio of the transition metal oxide to the organic hole transport material can improve the stability and hole injection performance of the composite material.

[0055] The present application also provides a method for preparing a composite material, see Figure 1 , Figure 1 This is a flow chart of an embodiment of a method for preparing a composite material provided in the present application, which specifically includes the following steps: Step S11: providing a first mixture, wherein the first mixture includes an organic hole transport material and a first solvent; Step S12: after subjecting the first mixture to a first light treatment, adding an organic transition metal salt to the first mixture, and continuing the second light treatment to obtain a composite material; wherein the valence band energy level of the transition metal oxide corresponding to the organic transition metal salt is higher than the valence band energy level of the organic hole transport material.

[0056] In one embodiment, the organic transition metal salt includes an organic anion and a transition metal cation.

[0057] In this embodiment, the first mixture is subjected to a first light treatment, and the organic hole transport material can excite electrons (e-) under light, and the electrons can react with oxygen and water in the first mixture system to generate hydroxide. After the organic transition metal salt is added to the system, the transition metal cations in the organic transition metal salt can react with the hydroxide to generate transition metal oxides, and the second light treatment is continued, which can continuously promote the generation of electrons and improve the efficiency of the photocatalytic reaction. The method of this embodiment can generate transition metal oxides in situ. Among them, the reaction mechanism can be referred to as follows:

[0058]

[0059] Among them, the transition metal cation (M n+ ) can be copper ions (Cu 2+ ), cobalt ions (Co 2+ ), molybdenum ion (Mo 3+ 、Mo 4+ Or Mo 6+ ), manganese ion (Mn 2+ The corresponding transition metal oxide may be one or more of copper oxide, cobalt oxide, molybdenum oxide, and manganese oxide.

[0060] In this embodiment, the valence band energy level of the transition metal oxide formed by the organic transition metal salt is higher than the valence band energy level of the organic hole transport material. Therefore, when used as the material of the hole functional layer, the valence band energy level of the transition metal oxide is between the organic hole transport material and the anode, which can reduce the hole injection barrier and improve the hole injection and transport performance.

[0061] Furthermore, through the photocatalysis of the organic hole transport material, the transition metal cations in the organic transition metal salt are prompted to generate transition metal oxides in situ, and the organic anions in the organic transition metal salt can be connected to the surface of the transition metal oxide generated in situ, thereby reducing the defects of the transition metal oxide, improving the hole injection and transport performance of the composite material, and effectively avoiding the regrowth and agglomeration of the nanoparticles of the transition metal oxide, thereby improving the uniformity and film-forming performance of the particles in the composite material.

[0062] In addition, during the light treatment process, the holes (h+) generated by photocatalysis can effectively fill the defects on the surface of the transition metal oxide (such as oxygen vacancies, etc.), play a role in passivating the transition metal oxide, and can effectively avoid the regrowth of nanoparticles of the transition metal oxide, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus improve the film-forming property of the composite material.

[0063] In the step S11: the organic hole transport material can refer to the relevant description of the composite material described above, which is not repeated here. In one embodiment, the concentration of the organic hole transport material in the first mixture is 4 to 12 mg / mL, specifically 4 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, etc.

[0064] The first solvent includes one or more of an alcohol solvent with 1 to 8 carbon atoms, an ether solvent with 1 to 8 carbon atoms, tetrahydrofuran, acetone, chlorobenzene, toluene, etc. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, n-octanol, etc. The ether solvent includes one or more of methyl ether, ethyl ether, etc.

[0065] In one embodiment, the first mixture also includes a hole sacrificial agent, which can consume the holes generated by photocatalysis, thereby providing more electrons to generate hydroxide. Further, the hole sacrificial agent can include one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, lactic acid, etc. In one embodiment, the mass ratio of the hole sacrificial agent to the organic hole transport material can be (0.5-1.5):5, specifically (0.5-1.3):5, (0.8-1.3):5, (0.8-1.0):5, (0.5-0.8):5, (1.3-1.5):5, etc. The mass ratio can provide an excess of the hole sacrificial agent to consume the holes generated in the photocatalytic reaction, and also avoid the waste of the hole sacrificial agent.

[0066] It can be understood that when the first solvent included in the first mixture includes solvent types listed in the hole sacrificial agent such as methanol and ethanol, the first solvent can have the function of a hole sacrificial agent and can consume holes, and at this time, there is no need to add the hole sacrificial agent additionally.

[0067] In the step S12: an organic transition metal salt is added to the first mixture, wherein the mass ratio of the organic transition metal salt to the organic hole transport material is (1-3):10, i.e. (10-30):100, and specifically can be (10-25):100, (15-25):100, (15-20):100, (10-15):100, (25-30):100, etc. The mass ratio can provide enough of the organic transition metal salt to form a transition metal oxide, thereby improving the film-forming property of the composite material, making the composite material include a gradient valence band energy level, reducing the hole injection barrier, and improving hole injection and transport. And provide enough organic anions to coordinate and connect to the transition metal oxide, reduce the surface defects of the transition metal oxide, and improve the film-forming property of the composite material.

[0068] In one embodiment, the organic transition metal salt includes the organic anion, and the organic anion can refer to the relevant description of the organic group mentioned above, which will not be repeated here.

[0069] In one embodiment, the transition metal cation may include a copper ion (Cu 2+ ), cobalt ions (Co 2+ ), molybdenum ion (Mo 3+ 、Mo 4+ Or Mo 6+ ), manganese ion (Mn 2+). In a specific embodiment, the organic transition metal salt includes an organic copper salt, which may specifically include one or more of 2-ethylhexanoic acid copper (II), monobutyl phthalate copper (II), methacrylate copper (II), hexane butyrate copper (II), 8-hydroxyquinoline copper (II), etc. Wherein "II" indicates that the valence of copper is +2. In a specific embodiment, the organic transition metal salt includes an organic cobalt salt, which may specifically include: 2-ethylhexanoic acid cobalt (II), bis (ethylcyclopentadiene) cobalt (II), naphthenate cobalt (II), neodecanoate cobalt (II), benzoate cobalt (II), etc. One or more. In a specific embodiment, the organic transition metal salt includes an organic molybdenum salt, which may specifically include tri (N-butylene-3,5-dimethylaniline) molybdenum, 2-ethylhexanoic acid molybdenum, bis (tert-butylimino) bis (dimethylamino) molybdenum, etc. One or more. Wherein, the valence of molybdenum can be +3, +4 or +6. In a specific embodiment, the organic transition metal salt includes an organic manganese salt, which may specifically include one or more of cyclohexanebutyrate manganese (II), 2-ethylhexyl manganese (II), 8-hydroxyquinoline manganese (II), etc. "II" indicates that the valence state of manganese is +2.

[0070] In one embodiment, the organic transition metal salt is added to the first mixture in the form of a solution. Specifically, the second solvent corresponding to the organic transition metal salt may include one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, and toluene. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, and n-butanol. The ether solvent includes one or more of methyl ether and ethyl ether.

[0071] In one embodiment, the organic transition metal salt is added while the first mixture is in a stirring state to improve the mixing uniformity of the first mixture and the organic transition metal salt, thereby promoting the generation of transition metal oxides.

[0072] In one embodiment, the time of the first light treatment is 1 to 2 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, etc. In one embodiment, the first light treatment is full-spectrum light treatment, that is, full-band irradiation is adopted. In one embodiment, the wavelength range of the first light treatment is 200 to 2500nm, such as one or more of 200 to 380nm, 380 to 760nm, 760 to 2500nm, etc. In one embodiment, the first light treatment may include one or more of the ultraviolet light band (UV for short, wavelength 200 to 380nm), the visible light band (VL for short, wavelength 380 to 760nm) or the infrared light band (IR for short, wavelength 760 to 2500nm). In one embodiment, the light source of the first light treatment may be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source of the first light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp may be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.

[0073] In one embodiment, during the first light treatment, the first mixture is in a stirring state to improve mixing uniformity, improve light uniformity, and improve heat dissipation. In one embodiment, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0 to 30°C, such as 0 to 4°C, 4 to 20°C, 20 to 25°C, 25 to 30°C, etc. Specifically, the first mixture can be protected by circulating condensed water to control the temperature of the first mixture within a preset range to avoid excessive temperature of the first mixture due to heat generation from light.

[0074] The second light irradiation treatment time is 4 to 8 hours, specifically 5 to 8 hours, 5 to 7 hours, 6 to 7 hours, 7 to 8 hours, etc. The second light irradiation treatment within the time range can photocatalytically obtain the preset loading of the transition metal oxide.

[0075] In one embodiment, the second light treatment is full-spectrum light treatment, that is, full-band irradiation is used. In one embodiment, the wavelength range of the second light treatment is 200-2500nm, such as one or more of 200-380nm, 380-760nm, 760-2500nm, etc. In one embodiment, the second light treatment may include one or more of ultraviolet light band (UV for short, wavelength 200-380nm), visible light band (VL for short, wavelength 380-760nm) or infrared light band (IR for short, wavelength 760-2500nm). In one embodiment, the light source of the second light treatment can be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source of the second light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp can be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.

[0076] In one embodiment, an organic transition metal salt is added to the first mixture to obtain a second mixture, and a second light treatment is continued. During the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0 to 30°C, such as 0 to 4°C, 4 to 20°C, 20 to 25°C, 25 to 30°C, etc. Specifically, the second mixture can be protected by circulating condensed water to control the temperature of the second mixture within a preset range to avoid excessive temperature of the second mixture due to heat generation from light.

[0077] In one embodiment, an organic transition metal salt is added to the first mixture to obtain a second mixture, and during the second light treatment, the second mixture can be in a stirring state to improve the mixing uniformity and the rate of generating transition metal oxides. In one embodiment, after the second light treatment, it also includes: using a cleaning agent to perform sedimentation washing on the mixture N times, N is an integer greater than or equal to 2, such as washing three times, etc. The cleaning agent may include one or more of ethyl acetate and acetone. In this embodiment, unreacted reactants, such as unreacted organic transition metal salts, etc., can be removed by multiple washings.

[0078] The present application provides a light emitting device, referring to Figure 2 , Figure 2The present application provides a structural schematic diagram of an embodiment of a light-emitting device, wherein the light-emitting device 100 includes a first electrode 10 and a second electrode 20 that are arranged opposite to each other, and a light-emitting layer 30 that is arranged between the first electrode 10 and the second electrode 20, and a hole functional layer 40 is arranged between the first electrode 10 and the light-emitting layer 30, wherein the material of the hole functional layer 40 includes the composite material provided in the present application, or includes a composite material obtained by the preparation method of the composite material provided in the present application.

[0079] In this embodiment, the material of the hole functional layer 40 includes a composite material, that is, an organic hole transport material and a transition metal oxide. The composite material and the inorganic material are combined to improve the stability of the composite material and the hole functional layer 40, so that the hole functional layer 40 has good hole transport performance and also has good hole injection performance. The valence band energy level of the transition metal oxide is higher than the valence band energy level of the organic hole transport material. By setting the composite material with a gradient valence band energy level in the hole functional layer 40, the valence band energy level of the transition metal oxide is between the organic hole transport material and the material of the first electrode 10, thereby reducing the hole injection barrier and improving the hole injection performance.

[0080] Furthermore, in the composite material, the surface of the transition metal oxide is connected with a negatively charged organic group, and the organic group is coordinated and connected to the surface of the transition metal oxide, and can combine with a large number of oxygen defects on the surface of the transition metal oxide, reduce the surface defects of the transition metal oxide, increase the dispersibility of the transition metal oxide, and improve the film-forming property of the composite material, thereby improving the film uniformity and density of the hole functional layer 40, reducing and avoiding the leakage current phenomenon of the light-emitting device 100, improving the stability of the light-emitting device 100, and reducing the interface barrier between the hole functional layer 40 and the adjacent film layer, thereby further improving the hole injection and transmission performance. In addition, the organic group is coordinated and connected to the surface of the transition metal oxide, which can also increase the carrier concentration and improve the hole transmission performance of the hole functional layer 40.

[0081] In one embodiment, the material of the hole functional layer 40 is composed of the composite material. Further, the hole functional layer 40 is a single-layer film structure. In this embodiment, the composite material is used as the material of the hole functional layer 40, and the performance of hole injection and hole transport can be achieved through the single-layer hole functional layer 40. In other embodiments, the material of the hole functional layer 40 may include other materials such as metal elements in addition to the composite material.

[0082] In one embodiment, in the thickness direction of the hole functional layer 40, the concentration of the organic hole transport material increases or decreases, the concentration of the transition metal oxide also increases or decreases, and the concentration of the organic hole transport material and the concentration of the transition metal oxide change in opposite trends.

[0083] In a specific embodiment, in the direction from the first electrode 10 to the light-emitting layer 30, the concentration of the organic hole transport material in the hole functional layer 40 shows an increasing trend, and the concentration of the transition metal oxide shows a decreasing trend. In this specific embodiment, the concentration or content of the transition metal oxide near the first electrode 10 is relatively high, that is, the side of the hole functional layer 40 near the first electrode 10 is equivalent to the hole injection layer, and the concentration or content of the organic hole transport material near the light-emitting layer 30 is relatively high, that is, the side of the hole functional layer 40 near the light-emitting layer 30 is equivalent to the hole transport layer, so that the functions of the two layers of hole transport and hole injection are realized through one layer of the hole functional layer 40, reducing the process of preparing the light-emitting device 100 and avoiding mutual damage between the two-layer structure of the traditional hole transport layer and the hole injection layer. In one embodiment, the thickness of the hole functional layer is 15-40 nm, specifically 15-35 nm, 20-35 nm, 20-30 nm, 25-30 nm, 15-20 nm, 35-40 nm, etc.

[0084] In one embodiment, the material of the light-emitting layer 30 is selected from organic light-emitting materials or quantum dot light-emitting materials.

[0085] The organic light-emitting material may be selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light;

[0086] The quantum dot luminescent material can be selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdS At least one of dZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, Sn At least one of PbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb , GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS;

[0087] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.

[0088] In one embodiment, the quantum dot luminescent material includes one or more of red quantum dots, green quantum dots, and blue quantum dots. The thickness of the luminescent layer 30 may be 5 to 100 nm, specifically 5 to 15 nm, 15 to 30 nm, 15 to 35 nm, 25 to 35 nm, 25 to 30 nm, 30 to 50 nm, 50 to 100 nm, etc.

[0089] In a specific embodiment, the quantum dots are selected from oily quantum dots, and the surface of the quantum dots is connected with a ligand that is easily soluble in a solvent with low polarity, including at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. As a specific embodiment, the acid ligand is at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand is at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octadecylamine; the (oxygen) phosphine ligand is at least one of trioctylphosphine and trioctylphosphine oxide.

[0090] In one embodiment, the light emitting device 100 may further include an electronic functional layer 50, and the electronic functional layer 50 is disposed between the second electrode 20 and the light emitting layer 30. In one embodiment, the electronic functional layer 50 may include one or both of an electron injection layer 51 and / or an electron transport layer 52; when the electronic functional layer 50 includes the electron injection layer 51 and the electron transport layer 52, the electron injection layer 51 is disposed close to the second electrode 20, and the electron transport layer 52 is disposed close to the light emitting layer 30.

[0091] In one embodiment, the material of the electron transport layer 52 includes doped or undoped inorganic nanocrystals, wherein the undoped inorganic nanocrystals are selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, SiO2, Ga2O3, ZrO2, NiO, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO3, Rb2CO3, RbBr, LiF, LiF / Yb, MgP, and MgF2; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y. In one embodiment, the material of the electron injection layer 51 can be a material known in the art for electron injection layer, for example, it can be selected from but not limited to at least one of LiF, MgP, MgF2, Al2O3, Ga2O3, LiF / Yb, ZnO, Cs2CO3, RbBr, and Rb2CO3.

[0092] In one embodiment, the first electrode 10 and the second electrode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, I At least one of TZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three stacked layers consisting of an AZO layer, an Ag layer, and an AZO layer.

[0093] The first electrode 10 and the second electrode 20 are a pair of electrodes. In one embodiment, the first electrode 10 is an anode, and the second electrode 20 is a cathode. It is understood that in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer. It is understood that the material and thickness of each layer of the light-emitting device 100 may be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100.

[0094] The light emitting device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.

[0095] It can be understood that the light-emitting device 100 can be an upright light-emitting device or an inverted light-emitting device. When the light-emitting device 100 is an upright light-emitting device, the substrate is combined with the side of the first electrode 10 away from the light-emitting layer 30. When the light-emitting device 100 is an inverted light-emitting device, the substrate is combined with the side of the second electrode 20 away from the light-emitting layer 30. It can be understood that in addition to the above-mentioned functional layers, the light-emitting device 100 can also be provided with some functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer. It can be understood that the materials and thicknesses of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100.

[0096] The present application also provides a method for preparing a light emitting device, see Figure 3 , Figure 3 The present invention provides a flow chart of a method for preparing a light-emitting device according to an embodiment of the present invention, which specifically includes the following steps:

[0097] Step S21: providing a preset device, wherein the preset device includes a first electrode;

[0098] Step S22: Arranging a hole functional material on the preset device to form a hole functional layer;

[0099] Step S23: forming a stacked light-emitting layer and a second electrode on the hole functional layer to obtain a light-emitting device.

[0100] The light-emitting device prepared in this embodiment is an upright device.

[0101] In one embodiment, the light-emitting device includes an electronic functional layer, and the step S23 specifically includes: forming a stacked light-emitting layer, an electronic functional layer and a second electrode on the hole functional layer to obtain the light-emitting device.

[0102] See also Figure 4 , Figure 4 This is a flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application. The method for preparing a light-emitting device in this embodiment comprises the following steps:

[0103] Step S31: providing a prefabricated device, wherein the prefabricated device comprises a stacked second electrode and a light-emitting layer;

[0104] Step S32: Arranging a hole functional material on the preset device to form a hole functional layer;

[0105] Step S33: forming a stacked first electrode on the hole functional layer to obtain a light-emitting device.

[0106] The light-emitting device prepared in this embodiment is an inverted device.

[0107] In one embodiment, the light-emitting device includes an electronic functional layer, and the step S31 specifically includes: providing a prefabricated device, wherein the prefabricated device includes a stacked second electrode, an electronic functional layer, and a light-emitting layer.

[0108] In the above two embodiments, the hole functional material includes the composite material provided in the present application, or includes a composite material obtained by the method for preparing the composite material provided in the present application. For details, please refer to the relevant description above, which will not be repeated here. In a specific embodiment, the hole functional material is the composite material provided in the present application, or is a composite material obtained by the method for preparing the composite material provided in the present application.

[0109] In one embodiment, in step S22 and step S32, the composite material may be disposed on the prefabricated device by a solution method. Specifically, the solution method may be a spin coating method, a printing method, an inkjet printing method, a doctor blade method, a printing method, a dip-coating method, a soaking method, a spray coating method, a roll coating method, a casting method, a slit coating method, a strip coating method, and the like.

[0110] In a specific embodiment, in step S22 and step S32, the composite material is arranged on the preset device to form a hole functional layer, including: a third mixture is arranged on the preset device, wherein the third mixture includes the composite material and a third solvent. Specifically, the third solvent may include an alcohol solvent, specifically one or more of methanol, ethanol, isopropanol, n-butanol, etc. Further, the concentration of the composite material in the third mixture may be 10-30 mg / mL, specifically 15 mg / mL, 20 mg / mL, 25 mg / mL, etc.

[0111] After the third mixture is prepared by the solution method, it is necessary to dry it to remove the third solvent. The drying can be heating drying or vacuum drying. The heating drying temperature can be 60 to 80°C and the time can be 20 to 60 minutes. The vacuum drying pressure is 10 -1 ~10 -2 Pa. Furthermore, the vacuum drying temperature may be room temperature (about 25° C.).

[0112] In this embodiment, the organic hole transport material is an organic macromolecule and has a lower surface energy than the transition metal oxide. After the third mixture containing the composite material is set on the preset device, during the volatilization and removal of the third solvent in the third mixture, the organic hole transport material with lower surface energy will tend to move away from the preset device, while the transition metal oxide tends to move toward the preset device, so that in the formed hole functional layer, in the thickness direction, the concentration of the organic hole transport material increases or decreases, the concentration of the transition metal oxide also increases or decreases, and the concentration of the organic hole transport material and the concentration of the transition metal oxide change in the opposite trend.

[0113] In other embodiments, the composite material may be disposed on the prefabricated device by other methods known in the art, such as sputtering, etc. In each embodiment of the above-mentioned preparation method, the electron transport layer, the hole functional layer, the light-emitting layer, the first electrode, etc. may refer to the corresponding description of the light-emitting device 100 in the above text, and will not be described in detail here.

[0114] In the light-emitting device provided in the present application, the preparation methods of the first electrode, the second electrode, the light-emitting layer, the hole functional layer, the electron functional layer and other film layers can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.

[0115] It is understood that the method for preparing the light-emitting device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.

[0116] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0117] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0118] Embodiment 1:

[0119] This embodiment provides a method for preparing a composite material and the prepared composite material, wherein the preparation method specifically comprises the following steps:

[0120] Step 1: TFB was added to chlorobenzene to obtain a 20 mg / mL TFB-chlorobenzene solution, and triethylamine was added to the TFB-chlorobenzene solution. The solution was then irradiated under a 300 W Xe lamp (full spectrum) for 1 hour under continuous stirring, during which time it was carried out under the protection of circulating condensed water at 4°C; wherein the mass ratio of triethylamine to TFB was 1:10.

[0121] Step 2: Under continuous illumination and stirring, 40 mg / mL 2-ethylhexanoate copper (II) chlorobenzene solution was added dropwise to the solution in step 1, wherein the mass ratio of 2-ethylhexanoate copper to TFB was 1:10; and the irradiation was continued for 4 hours, during which it was carried out under the protection of circulating condensed water at 4°C. After photodeposition, the above solution was washed three times by precipitation in excess ethyl acetate or acetone to wash away the excess copper salt to obtain a composite material.

[0122] Embodiment 2:

[0123] This embodiment is substantially the same as embodiment 1, except that in step 2, the mass ratio of copper 2-ethylhexanoate to TFB is 15:100.

[0124] Embodiment 3:

[0125] This embodiment is substantially the same as embodiment 1, except that in step 2, the mass ratio of copper 2-ethylhexanoate to TFB is 20:100.

[0126] Embodiment 4:

[0127] This embodiment is substantially the same as embodiment 1, except that in step 2, the mass ratio of copper 2-ethylhexanoate to TFB is 30:100.

[0128] Embodiment 5:

[0129] This embodiment is substantially the same as embodiment 1, except that in step 2, copper (II) monobutyl phthalate is added instead of copper 2-ethylhexanoate in embodiment 1.

[0130] Embodiment 6:

[0131] This embodiment is substantially the same as embodiment 1, except that in step 2, copper methacrylate (II) is added instead of copper 2-ethylhexanoate in embodiment 1.

[0132] Embodiment 7:

[0133] This example is substantially the same as Example 1, except that in step 2, copper (II) hexanebutyrate is added instead of copper 2-ethylhexanoate in Example 1, and the irradiation is continued for 6 hours.

[0134] Embodiment 8:

[0135] This example is substantially the same as Example 1, except that in step 2, 8-hydroxyquinoline copper (II) is added instead of 2-ethylhexanoate copper in Example 1, and the irradiation is continued for 8 hours.

[0136] Embodiment 9:

[0137] This embodiment is substantially the same as embodiment 1, except that in step 2, 2-ethylhexanoate cobalt (II) is added instead of 2-ethylhexanoate copper in embodiment 1.

[0138] Embodiment 10:

[0139] This embodiment is substantially the same as embodiment 1, except that in step 2, 2-ethylhexyl manganese (II) is added instead of copper 2-ethylhexanoate in embodiment 1.

[0140] Embodiment 11:

[0141] This embodiment is substantially the same as Embodiment 1, except that in step 2, tri(N-butylene-3,5-dimethylaniline) molybdenum is added instead of copper 2-ethylhexanoate in Embodiment 1.

[0142] Embodiment 12:

[0143] This embodiment is substantially the same as embodiment 1, except that in step 1, TPD is used instead of TFB in embodiment 1, and the mass ratio of copper 2-ethylhexanoate to TPD added in step 2 is 20:100.

[0144] Embodiment 13:

[0145] This embodiment is substantially the same as embodiment 1, except that in step 1, poly-TPD is used instead of TFB in embodiment 1, and the mass ratio of copper 2-ethylhexanoate to TPD added in step 2 is 20:100.

[0146] Comparative Example 1:

[0147] Step 1: Add an appropriate amount of cupric chloride to 30 ml of chlorobenzene to prepare a cupric chloride-chlorobenzene solution with a total concentration of 1 M, and add 0.015 mmol of sodium citrate to obtain a mixed solution A.

[0148] Step 2: Weigh an appropriate amount of sodium hydroxide and dissolve it in 5 ml of chlorobenzene solution to obtain an alkali solution; add the alkali solution to the mixed solution A according to a molar ratio of OH- to copper ions of 1.8:1 to form a mixed solution with a pH of 13, and then stir at 80°C for 1 hour to obtain a copper oxide nanoparticle solution.

[0149] Step 3: The copper oxide nanoparticles and TFB are mixed in a mass ratio of 10:100 and dissolved in chlorobenzene, and stirred for 2 hours to obtain a solution of a copper oxide-TFB mixed material.

[0150] Comparative Example 2:

[0151] Step 1: Weigh 150 mg of potassium permanganate and mix with 50 mL of chlorobenzene to obtain a precursor solution. Weigh 10 g of ammonium bicarbonate, place the precursor solution and ammonium bicarbonate in a closed environment (vacuum drying oven) in their respective beakers, and heat at 80°C for reaction. After the reaction is completed, centrifuge at 15,000 rpm for ten minutes to obtain manganese oxide nanoparticles.

[0152] Step 2: The manganese oxide nanoparticles and TFB are mixed in chlorobenzene at a mass ratio of 10:100, and stirred for 2 hours to obtain a solution of a manganese oxide-TFB mixed material.

[0153] Comparative Example 3:

[0154] Step 1: 10 mmol of ammonium molybdate and 300 mmol of thiourea (350 ml) were reacted in a reactor at 110°C for 2 hours, and finally filtered with a 0.22-micron microporous filter membrane. The lower layer of liquid was added to a dialysis bag with a molecular weight cutoff of 3500 and dialyzed for 3 days to obtain molybdenum oxide nanoparticles.

[0155] Step 2: The molybdenum oxide nanoparticles and TFB are mixed in chlorobenzene at a mass ratio of 10:100, and stirred for 2 hours to obtain a solution of a molybdenum oxide-TFB mixed material.

[0156] Device Example 1

[0157] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.

[0158] Step 1: Place the ITO glass sheet in a glass dish filled with ethanol solution, and ultrasonicate with acetone, deionized water, and ethanol for 20 minutes respectively, and then blow dry with a nitrogen gun; then place the cleaned ITO glass sheet in oxygen plasma for further cleaning for 10 minutes; continue to use UV-ozone to treat the surface of the ITO substrate for 15 minutes;

[0159] Step 2: Spin-coat the cleaned ITO glass sheets with a solution of the composite material of Example 1 (with a concentration of 20 mg / mL) in air, and anneal at 60° C. for 5 minutes in a glove box to obtain a hole functional layer with a thickness of 35 nm;

[0160] Step 3: Spin-coat Cd0.1ZnSe / Cd0.4Zn0.6Se / ZnSe / ZnS blue quantum dots on the hole transport layer at a spin-coating speed of 2000 r / min for 30 seconds; after spin-coating, anneal at 60 degrees Celsius in a glove box for 5 minutes to obtain a light-emitting layer;

[0161] Step 4: Spin-coat a ZMO ethanol solution (concentration of 30 mg / mL) on the light-emitting layer at a rotation speed of 3000 r / min for 30 seconds, and dry to obtain an electron transport layer with a thickness of 30 nm.

[0162] Step 5: Place the sample prepared in step 4 into a vacuum chamber, evaporate a top silver electrode with a thickness of 100 nm, and encapsulate.

[0163] Device Examples 2-13

[0164] Device Examples 2-13 are substantially the same as Device Example 1, with the only difference being that in step 2, the composite materials of Examples 2-13 are used respectively.

[0165] Device Comparison Examples 1-3

[0166] Device Examples 1-3 are basically the same as Device Example 1, with the only differences being that: in step 2, the solution of copper oxide-TFB mixed material in Comparative Example 1 is directly used, the solution of manganese oxide-TFB mixed material in Comparative Example 2 is used in step 2, and the solution of molybdenum oxide-TFB mixed material in Comparative Example 3 is used in step 2.

[0167] Device Comparison Example 4

[0168] The device embodiment of the present invention is substantially the same as the device embodiment 1, with the only difference being that: in step 2, the cleaned ITO glass sheet is spin-coated with PEDOT:PSS in air at a rotation speed of 3500 r / min for 30 seconds; after the spin coating, it is placed in air for annealing at a temperature of 150°C for 30 minutes to obtain a hole injection layer with a thickness of 25 nm; in a glove box with a nitrogen atmosphere, TFB-chlorobenzene solution (with a concentration of 8 mg / mL) is further spin-coated on the hole injection layer at a rotation speed of 3000 r / min for 30 seconds; after the spin coating, it is annealed in the glove box at a temperature of 180°C for 30 minutes to obtain a hole transport layer with a thickness of 30 nm; thereby, a hole functional layer including a hole injection layer and a hole transport layer is prepared.

[0169] Test 1:

[0170] In the process of preparing the quantum dot light-emitting diodes in device comparative example 1 and device example 2, after preparing the hole functional layer, an AFM (atomic force microscope) roughness test was performed on the hole functional layer, and the roughness of the hole functional layer was obtained. Figure 5 and Figure 6 ,in, Figure 5 and Figure 6 The AFM images of the hole functional layer in device comparative example 1 and device embodiment 2 respectively correspond to each other.

[0171] Depend on Figure 5 and Figure 6 It can be seen that the arithmetic average roughness (Ra) and root mean square roughness (Rq) of the hole functional layer in device embodiment 2 are much smaller than the arithmetic average roughness (Ra) and root mean square roughness (Rq) of the hole injection layer in device comparative example 1, respectively, indicating that the hole functional layer formed by the composite material provided in the present application has good film-forming property and surface uniformity. The composite material provided has good film-forming property, which may be due to the fact that the organic anion is connected to the surface of the transition metal oxide and can react with a large number of oxygen defects (O 2+ ) and effectively reduce the aggregation and regrowth of transition metal oxide particles, thereby improving the film-forming property of the composite material. It is also possible that during the preparation of the composite material, the holes (h+) generated by photocatalysis can effectively fill the defects (such as oxygen vacancies, etc.) on the surface of the transition metal oxide, play a role in passivating the transition metal oxide, and can effectively avoid the regrowth of transition metal oxide nanoparticles, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus also improve the film-forming property of the composite material.

[0172] Test 2:

[0173] The quantum dot light-emitting diodes of device embodiments 1-13 and device comparative examples 1-4 were tested for external quantum efficiency EQE and lifetime, and the data are shown in Table 1. Storage stability monitoring was also performed on device embodiments 2 and 12 and device comparative examples 1 and 4 to monitor the change of external quantum efficiency EQE with storage time, and see Table 1. Figure 7 , Figure 7 EQE-storage time diagram of device examples 2 and 12 and device comparative examples 1 and 4.

[0174] (1) The detection method of external quantum efficiency EQE is:

[0175] The ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, expressed in %, is an important parameter for measuring the quality of electroluminescent devices and can be obtained by measuring with an EQE optical test instrument. The specific calculation formula is as follows:

[0176]

[0177] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.

[0178] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0179] (2) The test method for life span T95@1000nit is: the time required for the brightness of the device to decrease to a certain proportion of the maximum brightness under constant current or voltage drive. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life span at 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:

[0180]

[0181] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of green QLED devices at rated brightness and found that the A value was 1.7.

[0182] Test 3:

[0183] According to the quantum dot light-emitting diodes of device examples 1-13 and device comparison examples 1-4, single hole devices (HOD) are prepared respectively, wherein the preparation method of the single hole device (HOD) is substantially the same as the preparation method of the corresponding complete QLED device, except that the electron transport layer is not prepared, and the obtained single hole device does not include the electron transport layer. The device structure of the single hole device (HOD) is: glass substrate / ITO / hole functional layer / QD light-emitting layer / Ag electrode.

[0184] The hole injection performance test method is:

[0185] A QLED efficiency test system was built by controlling QE PRO and Keithley 2400 through LabView. The system was used to test the current density-voltage curve (JV curve) of the single hole device (HOD). Figure 8 and Fig. 9 , Figure 8 and Fig. 9 JV curves of single hole devices of device examples 1-13 and comparative examples 1-4.

[0186] Through the current density-voltage curve, the space charge limited current (SCLC) region in the curve is obtained, and then according to the formula J = (9 / 8)ε r ε0μeV 2 / d 3 The hole mobility was calculated and the data are shown in Table 1. Where J represents the current density in mAcm -2 ; εr represents the relative dielectric constant, ε0 represents the vacuum dielectric constant; μ e Indicates hole mobility, unit: cm 2 V -1 s -1 ; V represents the driving voltage, unit is V; d represents the film thickness, unit is m.

[0187] Test 4:

[0188] The valence band energy levels of the copper oxide nanoparticles, molybdenum oxide nanoparticles and manganese oxide nanoparticles prepared in Comparative Examples 1, 2 and 3 were measured respectively.

[0189] Method for determining the valence band energy level: Use nanoparticles to prepare a dry film as the test sample. The film size is about 6*6mm and the thickness is less than 2mm. The Vance band (VB) spectrum is measured using a monochromatic He I light source (21.2eV) and a VG Scienta R4000 analyzer. The sample bias is -5V, and the secondary electron cutoff edge spectrum (SEC) is tested. Figure 10-12 , Figure 10-12 The valence band energy level diagrams are for copper oxide, molybdenum oxide and manganese oxide respectively. A similar method is used to determine the valence band energy level of cobalt oxide, such as Fig.13 , Fig.13 Valence band energy level diagram of cobalt oxide.

[0190] Table 1

[0191]

[0192]

[0193] It can be seen from Table 1 that compared with device comparison examples 1-3, the external quantum efficiency and lifespan of device embodiments 1-13 are significantly improved, indicating that the composite material provided in the present application as the material of the hole functional layer can have good hole transport and hole injection performance, improve the hole mobility of the light-emitting device, thereby improving the carrier injection balance of the light-emitting device, and further improving the external quantum efficiency and lifespan of the device.

[0194] It can be seen from device embodiments 1-4 that in the preparation process of the composite material, the mass ratio of the organic transition metal salt to the organic hole transport material is relatively small (for example, 10:100), which may have a small improvement in the performance of hole injection, and the amount of organic anions is relatively small, so that the effect on the film formation uniformity and surface smoothness of the hole functional layer is relatively small; while the mass ratio of the organic transition metal salt to the organic hole transport material is relatively large (for example, 30:100), so that relatively more transition metal oxides are produced, and relatively more organic anions are introduced, which may lead to a decrease in the conductivity of the device, affecting the efficiency of the light-emitting device to a certain extent.

[0195] Depend on Figure 7It can be seen that the device EQE changes after the complete device is placed in the air for 60 days. The device EQE of device comparison example 4 decreases by 27.64% after 60 days, while device examples 2 and 12 only decrease by 2.56% and 2.91%, respectively. This shows that the composite material provided in the present application and the composite material prepared by the method for preparing the composite material form a hole functional layer, and the light-emitting device including this hole functional layer has good storage stability, and the change in external quantum efficiency is small after 60 days of placement. This may be because when the hole transport layer and the hole injection layer are formed by the solution method in device comparison example 4, there may be mutual destruction of the film layers, such as dissolution leading to destruction, etc., which leads to poor stability of the light-emitting device. In the composite material prepared by the present application through the photocatalytic in-situ generation of transition metal oxides by organic hole transport layer materials, the transition metal oxides have high binding properties with the organic hole transport layer materials, and the functions of hole injection and hole transport can be realized by a single solution method setting, and the film layer is more uniform, the leakage current of the light-emitting device is smaller, and the light-emitting device is more stable. Combination Figure 5 and Figure 6 It can also be seen from the AFM film roughness that the surface of the hole functional layer of device embodiment 2 is smoother, that is, the film-forming property is better, which also makes the light-emitting device more stable.

[0196] from Figure 10-13 It can be seen that the valence band energy level of the introduced transition metal oxide is between -4.7 and -5.45 eV, and the position of the anode (ITO electrode) is usually around -4.7 eV. Therefore, the valence band energy level of the metal oxide introduced in this application is between the anode and the hole transport layer material, which can play a role in leveling the hole injection barrier, thereby improving the hole injection of the light-emitting device and improving the luminescence efficiency of the device.

[0197] The above experimental results show that the present application introduces inorganic transition metal oxides into the organic hole transport layer material in situ through photocatalytic technology, and introduces organic groups to connect to the transition metal oxides. Through the preparation of a layer of hole functional layer, a hole functional layer with uniform film layer, smooth surface, and good hole injection and hole transport properties can be formed, so that the light-emitting device has a better carrier injection balance, and thus has better luminous efficiency and life, as well as storage stability.

[0198] The composite materials and their preparation methods, light-emitting devices and their preparation methods, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: The invention comprises an organic hole transport material and a transition metal oxide, wherein the valence band energy level of the transition metal oxide is higher than the valence band energy level of the organic hole transport material.

2. The composite material according to claim 1, characterized in that The valence band energy level of the transition metal oxide is 0.2 to 0.4 eV higher than the valence band energy level of the organic hole transport material; And / or, the valence band energy level of the metal oxide is -4.7 to -5.4 eV; and / or, the valence band energy level of the organic hole transport material is -5.2 to -5.4 eV; and / or, the mass ratio of the transition metal oxide to the organic hole transport material is 1:4 to 20; And / or, the organic hole transport material includes N,N'-dinaphthyl-N,N'-diphenylbenzidine, N,N'-bis-(3-methylphenyl)-N,N'-bis-(phenyl)-benzidine), 4,4',4"-tris(N-3-methylphenyl-N-phenyl-amino)-triphenylamine, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(N,N'-bis(4-butylphenyl)-N,N'-bis One or more of poly(phenyl)benzidine), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazole-9-yl)triphenylamine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine; And / or, the transition metal oxide includes one or more of copper oxide, cobalt oxide, molybdenum oxide, and manganese oxide; And / or, the average particle size of the transition metal oxide is 3 to 10 nm; And / or, the transition metal oxide is connected to a negatively charged organic group, and the organic group is selected from one or more of the following structures: Wherein, R1, R3, and R4 are independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; R2 and R5 are selected from one or more combinations of H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; The substituents are selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkyl acyloxy, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, and C3-C10 cycloalkyl; n is an integer of 0-4, and m is an integer of 0-6.

3. The composite material according to claim 2, characterized in that Each occurrence of R1, R2, R3, R4, and R5 is independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C10 alkyl, substituted or unsubstituted C3-C10 cycloalkyl, substituted or unsubstituted C2-C10 alkenyl, substituted or unsubstituted C3-C10 cycloalkenyl, substituted or unsubstituted aryl having 6-12 ring atoms, and substituted or unsubstituted heteroaryl having 5-12 ring atoms; Wherein, the substituents are selected from one or more combinations of C1-C10 alkyl acyloxy, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, and C3-C10 cycloalkyl.

4. The composite material according to claim 2-3, characterized in that The organic group includes one or more of the following structural formulas:

5. A method for preparing a composite material, characterized in that: include: Providing a first mixture, wherein the first mixture includes an organic hole transport material and a solvent; After the first mixture is subjected to a first light treatment, an organic transition metal salt is added to the first mixture, and the mixture is subjected to a second light treatment to obtain a composite material; The valence band energy level of the transition metal oxide prepared from the organic transition metal salt is higher than the valence band energy level of the organic hole transport material.

6. The preparation method according to claim 5, characterized in that: The conduction band energy level of the first transition metal oxide is 0.2 to 0.4 eV higher than the valence band energy level of the organic hole transport material; And / or, the valence band energy level of the transition metal oxide is -4.7 to -5.4 eV; and / or, the valence band energy level of the organic hole transport material is -5.2 to -5.4 eV; And / or, the organic hole transport material includes N,N'-dinaphthyl-N,N'-diphenylbenzidine, N,N'-bis-(3-methylphenyl)-N,N'-bis-(phenyl)-benzidine), 4,4',4"-tris(N-3-methylphenyl-N-phenyl-amino)-triphenylamine, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(N,N'-bis(4-butylphenyl)-N,N'-bis One or more of poly(phenyl)benzidine), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazole-9-yl)triphenylamine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine; and / or, the mass ratio of the organic transition metal salt to the organic hole transport material is (1-3):10; and / or, the concentration of the organic hole transport material in the first mixture is 4 to 12 mg / mL; And / or, the first mixture further includes a hole sacrificial agent; And / or, the organic transition metal salt comprises an organic anion and a transition metal cation, and the organic anion is selected from one or more of the following structures: Wherein, R1, R3, and R4 are independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; R2 and R5 are selected from one or more combinations of H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; The substituent is selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkyl acyloxy, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, C3-C10 cycloalkyl; n is an integer of 0-4, and m is an integer of 0-6.

7. The preparation method according to claim 5, characterized in that: The organic anion includes one or more of the following structural formulas: And / or, the transition metal cations include one or more of copper ions, cobalt ions, molybdenum ions, and manganese ions; And / or, the solvent includes one or more of an alcohol solvent having 1 to 8 carbon atoms, an ether solvent having 1 to 8 carbon atoms, tetrahydrofuran, acetone, chlorobenzene, and toluene. And / or, the hole sacrificial agent includes one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, and lactic acid; And / or, the mass ratio of the hole sacrificial agent to the organic hole transport material is (0.5-1.5):

5.

8. The preparation method according to claim 5, characterized in that: The first light treatment adopts full spectrum irradiation; And / or, the first light treatment lasts for 1 to 2 hours; and / or, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30° C.; and / or, during the first light irradiation process, the first mixture is in a stirring state; And / or, the second light treatment uses full spectrum irradiation; And / or, the second light treatment time is 4 to 8 hours; And / or, after adding the organic transition metal salt to the first mixture, a second mixture is obtained, and during the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0-30° C. and the second mixture is in a stirring state.

9. A light emitting device, characterized in that: include: A first electrode and a second electrode arranged opposite to each other; A light-emitting layer is disposed between the first electrode and the second electrode; A hole functional layer, disposed between the first electrode and the light-emitting layer; Wherein, the material of the hole functional layer includes the composite material as described in any one of claims 1 to 5, or includes the composite material prepared by the preparation method of the composite material as described in any one of claims 6 to 10.

10. The light emitting device according to claim 9, characterized in that: In the direction from the first electrode to the light-emitting layer, the concentration of the organic hole transport material in the hole functional layer increases gradually, and the concentration of the transition metal oxide decreases gradually; And / or, the thickness of the hole functional layer is 15 to 40 nm; And / or, the material of the light-emitting layer is selected from an organic light-emitting material or a quantum dot light-emitting material; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot light-emitting material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, and the The II-VI compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, Cd ZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, Hg At least one of ZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb , at least one of GaPAs, GaPSb, AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; And / or, the first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, IT At least one of ZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; And / or, the light-emitting device also includes an electronic functional layer, which is arranged between the second electrode and the light-emitting layer, and the material of the electronic functional layer includes doped or undoped inorganic nanocrystals; wherein the undoped inorganic nanocrystals are selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, SiO2, Ga2O3, ZrO2, NiO, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO3, Rb2CO3, RbBr, LiF, LiF / Yb, MgP, MgF2; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y.